KEY PRINCIPLES AND STRATEGIES TEACHERS CAN USE TO IMPROVE LANGUAGE ACQUISITION AND PROFICIENCY IN YOUNG LEARNERS (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article explores the linguistic foundations of teaching a foreign language to elementary school students. It discusses key principles and strategies that educators can employ to support language acquisition and proficiency in young learners. The article emphasizes the importance of providing comprehensible input, encouraging language output, integrating language skills, fostering language awareness, creating authentic contexts for learning, promoting cultural competence, addressing individual differences, and providing assessment and feedback. By understanding and implementing these linguistic foundations, teachers can create a supportive and effective learning environment that facilitates language development and cultural understanding among elementary school students.